Case-based review of isolated tentorial hypoplasia with herniation: Applying Occam’s Razor - Tiwari, Mona; Jha , Shreyashi; Pendyala, Santosh K (Indian Journal of Case Reports, 2025)
Descriptions of isolated tentorium hypoplasia (TH) without any major clinical correlates have been confined to scarce clinical reports. This report entails the first case of an adult with a bilateral tentorial defect leading to herniation of bilateral occipital lobes, without any alarming neurological sequel. A 43‑year‑old gentleman presented to the outpatient department with a headache for 6 months. Neurological examination was normal. On neuroimaging, a “mass” was noted in the quadrigeminal and left superior cerebellar cistern. On careful evaluation, herniation of cuneus and precuneus in quadrigeminal plate cistern was observed bilaterally, more on the right side secondary to a bilateral defect in the superior part of tentorium cerebelli evident by non-visualization of the superior part associated with dilatation of posterior part of lateral ventricles. This case report aims to increase awareness about TH to prevent misdiagnoses along with careful follow-up so as not to dismiss the finding as clinically irrelevant. The sparse literature and vague clinical symptomatology contribute to inadequate identification of this entity.